4x-(-x+3)+3=5-2(3-4x)

Simple and best practice solution for 4x-(-x+3)+3=5-2(3-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(-x+3)+3=5-2(3-4x) equation:


Simplifying
4x + -1(-1x + 3) + 3 = 5 + -2(3 + -4x)

Reorder the terms:
4x + -1(3 + -1x) + 3 = 5 + -2(3 + -4x)
4x + (3 * -1 + -1x * -1) + 3 = 5 + -2(3 + -4x)
4x + (-3 + 1x) + 3 = 5 + -2(3 + -4x)

Reorder the terms:
-3 + 3 + 4x + 1x = 5 + -2(3 + -4x)

Combine like terms: -3 + 3 = 0
0 + 4x + 1x = 5 + -2(3 + -4x)
4x + 1x = 5 + -2(3 + -4x)

Combine like terms: 4x + 1x = 5x
5x = 5 + -2(3 + -4x)
5x = 5 + (3 * -2 + -4x * -2)
5x = 5 + (-6 + 8x)

Combine like terms: 5 + -6 = -1
5x = -1 + 8x

Solving
5x = -1 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
5x + -8x = -1 + 8x + -8x

Combine like terms: 5x + -8x = -3x
-3x = -1 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3x = -1 + 0
-3x = -1

Divide each side by '-3'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 4x[33-3x(5+2)]= | | 4x+3(3-2x)=3(-2+2x)-3x-7 | | 2x+4.7=7.5 | | r^2=-40+13r | | 3x-17=-32 | | (2/5)(1/5) | | 2b+4=-17.2 | | 8=4(7x+3) | | x-47-4x=5-7x-19+3x | | 2x-12x^2+32=0 | | 3r^2-122r+500=0 | | 0.5x+2=10 | | x*x+3x+4=5 | | P(x)=2x^4-3x^3-14 | | 58.3=10-8m | | x=1.333333333+-1.666666667y | | 117+45=180 | | 3(s)-5=27 | | .75n=-5.25 | | 19.19+n=26.19 | | -3(-3z+7)= | | -10-5x=8 | | 5.25n=-36.75 | | x-31-4x=5-7x-38+3x | | xty=-5 | | 2x^4+2x=37x+2 | | 4(x-5)2=36 | | 4(x-5)squared=36 | | 3xty=-21 | | 2x/3-1/6=5x/6-2/3 | | 3(-1+7x)=102 | | -9+7x-4x=0 |

Equations solver categories